1999
DOI: 10.1111/j.1151-2916.1999.tb01901.x
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Creep and Rupture of Silicon Nitride

Abstract: We have characterized the tensile creep, rupture lifetime, and cavitation behavior of a commercial, gas-pressuresintered silicon nitride in the temperature range 1150°to 1400°C and stress range 70 to 400 MPa. Individual creep curves generally show primary, secondary, and tertiary creep. The majority of the primary creep is not recoverable. The best representation of the data is one where the creep rate depends exponentially on stress, rather than on the traditional power law. This representation also removes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
1
28
0
2
Order By: Relevance
“…5) or 6 (Ref. 18) with increasing stress. Because n varies, some authors have suggested that the mechanism of creep deformation differs at high and low stresses.…”
Section: Introductionmentioning
confidence: 98%
“…5) or 6 (Ref. 18) with increasing stress. Because n varies, some authors have suggested that the mechanism of creep deformation differs at high and low stresses.…”
Section: Introductionmentioning
confidence: 98%
“…Q is the activation energy determined to be approximately 740 kJ/mol from literature [97,98]. R is the universal gas constant (8.31447 J/ (mol/°K)).…”
Section: §4 Conclusionmentioning
confidence: 99%
“…Como ejemplo, la figura 2 muestra este hecho en materiales a base de nitruro de silicio, deformados en compresión y en tracción (7,(15)(16)(17); un comportamiento análogo ha sido identificado en cerámicos a base de SiC (18) o de Al 2 O 3 (19) con fases secundarias. En cambio, los materiales monofásicos exhiben el mismo comportamiento en compresión y en tracción (14).…”
Section: Características De La Fluencia De Estos Materialesunclassified
“…Así, la mayor parte de los estudios atribuyen la fluencia en compresión del nitruro de silicio al deslizamiento de fronteras de grano acomodado por disolución-precipitación, si bien existen menciones a acomodación por fluencia viscosa (7). En tracción, en cambio, la deformación se produce generalmente por cavitación acomodado por el deslizamiento relativo de los granos (7,16,17) o por un mecanismo combinado (7,21). Esta afirmación está apoyada por la observación sistemática de que la fracción volumétrica de cavidades aumenta linealmente con la deformación (7,(15)(16)(17)20).…”
Section: Cerámicas No Oxídicas: Si 3 Nunclassified